Product and Promotion Adaptation by European Firms in the U.S - Ward, James J. (Journal of International Business Studies, 1973)
European subsidiaries surveyed in this study exhibit a strong tendency to adapt products and promotion strategies to U.S. markets. While most products are adapted in some manner, changes and their costs are relatively minor.